观看短视频作为教学辅助的有效性析 —以 Golden Bee Preschool and Kindergarten 幼儿园汉语课堂为例 - Nelly, Nelly; Iden, Sabinus (Journal of Maobi, 2024)
Listening is crucial in language learning, especially when learning Chinese. Listening, speaking, reading, and writing are the four essential skills in language learning, and language learning typically begins with listening. Short videos, as an auxiliary teaching tool, leverage the advantages of audiovisual learning and show clear effectiveness. To achieve the research objectives, I used experimental and testing methods. The study focused on students aged 4-6, starting with a pre-test. Subsequently, while explaining new vocabulary, students were provided with 15 minutes of relevant videos. Finally, a post-test was conducted. The results show that using videos as auxiliary teaching tools in kindergarten Chinese courses is highly effective, with students' progress in learning Chinese improving by an average of 75%. Using short videos as a teaching method can effectively enhance students' interest and motivation in learning.